Antenatal diagnosis of alobar holoprosencephaly - Khanna, Dolly; Bhatti, Karandeep S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Holoprosencephaly (HPE), a congenital induction disorder, occurs due to failed segmentation of neural tube and subsequent incomplete separation of the prosencephalon. Because of the defect in the ventral induction, HPE is also associated with multiple facial abnormalities. Mortality correlates with the severity of brain malformation and facial phenotype. Frequent causes of death include respiratory infections, dehydration due to uncontrolled diabetes insipidus, intractable seizures, and brainstem malfunction. This is a case of Alobar holoprosencephaly in the fetus of a 31-year-old G2P1 female, detected on level II obstetric ultrasound at 17 weeks of gestation. The objective of this case report is to discuss the etiology, pathogenesis, prenatal sonographic findings, management and prognosis of HPE which can aid in its early antenatal diagnosis and can help formulate an adequate plan for the parents and fetus.